(untitled) (Economic and Political Thought, 2011)
The article presents basic principles of risk management, i.e. risk identification and analysis, risk assessment and specification of its variants, and methods of risk limitation and elimination. It highlights an issue of increasing information resources of various fields and branches of economy. It extensively discusses an issue of how to effectively counteract diversified risk. The theoretical presentation of Risk Management was illustrated by examples originating from international trade.